On the dynamic response of rolling base isolation systems. Issue 4 (20th November 2012) - Foti, D.; Catalan Goni, A.; Vacca, S.
SUMMARY In the present paper, the dynamic behavior of a rolling isolation device composed of cylinders moving in between two rubber layers is studied from a theoretical point of view. The device reduces the seismic energy both by decoupling the motion of the structure from the base and through the visco‐elastic behavior of the rubber (or neoprene). The behavior and the efficacy of this device is explained by relations obtained for the rolling friction coefficient versus the rolling velocity and for the horizontal force versus the vertical load acting on the device. Future studies will aim to determine the appropriate dimensions of the elements composing the isolator that most reduce seismic vibrations in structures. Copyright © 2012 John Wiley & Sons, Ltd.